Differences in Emotional Intelligence Between Male and Female Nursing Students From a Population With a Low Percentage of Male Nurses - Karol Laskowski RN, PhD; Justyna Paszkiewicz RN, PhD; Adam Szepeluk PhD; Kamil K. Hozyasz MD, PhD (SAGE Publishing, 2024)
Introduction Poland has the largest shortage of nurses in Europe, as well as a low percentage of male nurses. Information relating to emotional intelligence has been explored to determine whether it predicts the characteristics and outcomes of qualified health professionals during their academic training and practice. Objective This study aimed to measure differences in emotional intelligence between male and female nursing students. Participants and methods In this cross-sectional study, emotional intelligence was measured using the Schutte Self-Report Emotional Intelligence Test (SSEIT) in 21 male and 127 female nursing students from John Paul II University in Biała Podlaska, Poland. Results The raw overall scores of emotional intelligence in male and female students were similar. Differences were observed after the conversion of raw scores into normalized (sten) scores. High normalized scores (sten 8-10) of emotional intelligence had every third of male students and only 14.2% of female students. The lowest sten values of emotional intelligence in male and female students were 3 and 1, respectively. Less than 10% of male students and over 20% of female students had low normalized scores (sten ≤3) for emotional intelligence and an isolated ability to recognize emotions (factor II). Conclusions The emotional intelligence expressed in normalized scores was higher in male nursing students than in female nursing students. This evidence may suggest that, at the stage of choosing a field of study, Polish male nursing students self-select for the nursing profession, at least in terms of emotional intelligence. The influx of men into the profession should be considered as a positive trend.